Fully dense hot pressed calcium cobalt oxide ceramics. Issue 6 (15th April 2018) - Puri, Nidhi; Tandon, Ram P.; Mahapatro, Ajit K.
Abstract: The processing parameters have been optimized to achieve highly pure and fully dense pellets of calcium cobalt oxide (Ca3 Co4 O9 ) from solid-state ball milled calcium carbonate and cobalt oxide mixtures, calcined at optimized temperature and time, and consolidated by hot-pressing. The microscopic, spectroscopic, and thermal analysis suggest samples with longer ball-milling time require less calcination time for synthesizing highly pure crystalline phases of Ca3 Co4 O9, and provide 99.2 ± 0.5% relative density. Graphical abstract: fx1